Are low cholesterol values associated with excess mortality?. Issue 6466 (9th February 1985) - Salmond, C E; Beaglehole, R; Prior, I A
Abstract : The relation between cholesterol concentration and mortality was studied prospectively over 17 years in 630 New Zealand Maoris aged 25-74. The dead or alive state of each person was determined in 1981. The causes of death were divided into three categories: cancer, cardiovascular disease, and "other." Using univariate and both linear and non-linear multivariate methods of analysis for survivorship data, significant inverse relations with serum cholesterol were found for total mortality in women, for mortality from cancer in men and women, and for other causes of mortality in both men and women. The inverse and non-linear association with total mortality in women remained significant when deaths in the first five years of follow up were excluded. This suggests that the association was not explained by undetected illness causing low cholesterol concentrations at the time of initial examination.